2019
DOI: 10.1097/md.0000000000014520
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of trigger point dry needling versus sham needling for chronic tension-type headache

Abstract: Background: In this randomized, double-blind, parallel-group trial, we aimed to explore the effectiveness of trigger point dry needling in patients with chronic tension-type headache in reducing headache frequency, intensity and duration, and improvement of health-related quality of life. Methods: The 168 patients in 2 neurology clinics with chronic tension-type headache. The participants were randomly assigned to one of two treatment groups for dry needling or sham dry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 17 publications
2
44
0
5
Order By: Relevance
“…Sedighi et al compared superficial (skin-biased) versus deep (muscle-biased) dry needing over the suboccipital and upper trapezius musculature in people with CeH and showed that both needling approaches were similarly effective for reducing headaches, but deep dry needling was more effective for improving function [55]. A recent randomized clinical trial found that real dry needling over active TrPs located in the neck and head musculature was more effective than sham needling for reducing headache pain parameters, e.g., intensity, frequency, and duration of headache, and for improving health-related quality of life in patients with chronic TTH [56]. Nevertheless, the number of sessions, muscles which should be needled, dosage, frequency of sessions, and long-term follow-ups are needed to further conclude a real effect of dry needling in primary headaches.…”
Section: Scientific Evidence Of Needling Therapies Interventions For mentioning
confidence: 99%
“…Sedighi et al compared superficial (skin-biased) versus deep (muscle-biased) dry needing over the suboccipital and upper trapezius musculature in people with CeH and showed that both needling approaches were similarly effective for reducing headaches, but deep dry needling was more effective for improving function [55]. A recent randomized clinical trial found that real dry needling over active TrPs located in the neck and head musculature was more effective than sham needling for reducing headache pain parameters, e.g., intensity, frequency, and duration of headache, and for improving health-related quality of life in patients with chronic TTH [56]. Nevertheless, the number of sessions, muscles which should be needled, dosage, frequency of sessions, and long-term follow-ups are needed to further conclude a real effect of dry needling in primary headaches.…”
Section: Scientific Evidence Of Needling Therapies Interventions For mentioning
confidence: 99%
“…TrPs can be defined as hyperirritable palpable spots of taut fibers located within a myofascial tissue, which have been known to cause non-dermatomal referral pain and discomfort [21]. Muscles which are commonly involved in tension-type headache include the sub-occipital, sternocleidomastoid, upper trapezius, levator scapula, splenius, temporalis, and masseter [14, 22, 23].…”
Section: Introductionmentioning
confidence: 99%
“…Some compared acupuncture to sham while others with other techniques. Three studies utilized dry needling, and they were all evaluated as moderate methodological quality (Karakurum et al [ 19 ], Gildir et al [ 20 ], Kamali et al [ 21 ]). Moreover, three studies researched the effects of electroacupuncture, and all of them were evaluated as high quality (Xue et al [ 22 ], Chassot et al [ 23 ]), with one of them scoring 10/10 on the PEDro scale (Wang et al [ 24 ]).…”
Section: Resultsmentioning
confidence: 99%